Distinctive microRNA expression profiles in CD34+ bone marrow cells from patients with myelodysplastic syndrome - Dostalova Merkerova, Michaela; Krejcik, Zdenek; Votavova, Hana; Belickova, Monika; Vasikova, Alzbeta; Cermak, Jaroslav (European journal of human genetics, 2011)
MicroRNAs (miRNAs) are small non-coding RNAs functioning as regulators of hematopoiesis. Their differential expression patterns have been linked with various pathological processes originating from hematopoietic stem cells (HSCs). However, limited information is available regarding the role of miRNAs in myelodysplastic syndrome (MDS). Using miRNA arrays, we measured expression of 1,145 miRNAs in CD34+ bone marrow cells obtained from 39 MDS and acute myeloid leukemia (AML) evolved from MDS patients, and compared them with those of six healthy donors. Differential miRNA expression was analyzed and a panel of upregulated (n=13) and downregulated (n=9) miRNAs were found (P<0.001) in MDS/AML patients. An increased expression of a large miRNA cluster mapped within the 14q32 locus was detected. Differences in miRNA expression of MDS subtypes showed a distinction between early and advanced MDS; an apparent dissimilarity was observed between RAEB-1 and RAEB-2 subtypes. In early MDS, we monitored upregulation of proapoptotic miR-34a, which may contribute to the increased apoptosis of HSCs. Patients with 5q deletion were characterized by decreased levels of miR-143(*) and miR-378 mapped within the commonly deleted region at 5q32. This is an early report describing differential expression in MDS CD34+ cells, likely reflecting their disease-specific regulation.
Keywords: senioři; Up-Regulation; Gene Expression Profiling; apoptóza; Analysis of Variance; Gene Deletion; Microarray Analysis; upregulace; mikro RNA; multigenová rodina; down regulace; hematopoéza; Middle Aged; Myelodysplastic Syndromes; mužské pohlaví; Antigens, CD34; Leukemia, Myeloid, Acute; Adult; mladý dospělý; analýza rozptylu; MicroRNAs; Down-Regulation; myelodysplastické syndromy; Multigene Family; delece genu; Young Adult; ženské pohlaví; mikročipová analýza; Humans; lidé středního věku; akutní myeloidní leukemie; stanovení celkové genové exprese; hematopoetické kmenové buňky; Hematopoiesis; dospělí; antigeny CD34; Female; Aged; Hematopoietic Stem Cells; lidé; Male; Apoptosis